A Fine Balance as An Indian Politic Background Representation - Assi Hussein, Ali (Integrated Journal for Research in Arts and Humanities, 2024)
This paper is a fine representation of '' a fine balance a novel written by Rohinton Mistry a major Indian writer, written in 1995, that described the Indian people in the period between 1970 to 1984 and all the side effects of the bad political system carried in that era. The project has been divided into an introduction containing a summary of the novel and a statement of the politics and the corruption of the government. One chapter that divided into two topics, the first one concerned the novel and the second concerned with corruption and weak politics in a wide scope. A conclusion that summarized the whole project in one paper that stated the idea of the writer.